Predictability of bitcoin returns. Issue 1 (2nd January 2022) - Cheah, Jeremy Eng-Tuck; Luo, Di; Zhang, Zhuang; Sung, Ming-Chien
Abstract : This paper comprehensively examines the performance of a host of popular variables to predict Bitcoin returns. We show that time-series momentum, economic policy uncertainty, and financial uncertainty outperform other predictors in all in-sample, out-of-sample, and asset allocation tests. Bitcoin returns have no exposure to common stock and bond market factors but rather are affected by Bitcoin-specific and external uncertainty factors.